Small is Successful!? A Study of Exit Behavior in a Declining Markets Experiment - Mathias Erlei; Jens-Peter Springmann (Technische Universität Clausthal, Abteilung für Volkswirtschaftslehre, 2006)
This paper provides experimental evidence on exit behavior of asymmetrically sized firms in a duopoly with declining demand. We conduct three treatments: (a) The basic model with indivisible real capital. The structure of this treatment represents the main findings of Ghemawat and Nalebuff (1985); (b) an extension of the basic model by introducing a bankruptcy constraint; (c) here we allow for divisible real capital (Ghemawat and Nalebuff (1990)). In all three treatments we find behavior that is, by and large, in line with subgame perfect Nash Equilibrium. However, there is a problem of multiplicity of equilibria in (b) and we find an anchor effect as well as learning effects in (c).
Keywords: D43; L11; C92; 330; Exit; duopoly; declining market; experimental economics